"I control my own emotions for the sake of the team": Emotional self-regulation and interpersonal emotion regulation among female high-performance curlers - Tamminen, K. A.; Crocker, P. R. E. (Psychology of Sport and Exercise, 2013)
Objectives: The purpose of this study was to examine emotional self-regulation and interpersonal emotion regulation within a team of competitive athletes.